2017
DOI: 10.3892/or.2017.5735
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenesis target therapy for advanced osteosarcoma

Abstract: Osteosarcomas (OS), especially those with metastatic or unresectable disease, have limited treatment options. The greatest advancement in treatments occurred in the 1980s when multi-agent chemotherapy, including doxorubicin, cisplatin, high-dose methotrexate, and, in some regimens, ifosfamide, was demonstrated to improve overall survival compared with surgery alone. However, standard chemotherapeutic options have been limited by poor response rates in patients with relapsed or advanced cases. It has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 119 publications
2
85
0
Order By: Relevance
“…VM represents one of the major causes for the development of resistance to anti‐angiogenic therapy in solid tumours, and it seems that VM is dependent on the most common pro‐angiogenic factors . In particular, the mechanisms responsible for resistance to anti‐angiogenic therapy have been widely investigated in human OSA and several studies underlining the role of Hsp90 have been carried out …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VM represents one of the major causes for the development of resistance to anti‐angiogenic therapy in solid tumours, and it seems that VM is dependent on the most common pro‐angiogenic factors . In particular, the mechanisms responsible for resistance to anti‐angiogenic therapy have been widely investigated in human OSA and several studies underlining the role of Hsp90 have been carried out …”
Section: Discussionmentioning
confidence: 99%
“…36,37 In particular, the mechanisms responsible for resistance to anti-angiogenic therapy have been widely investigated in human OSA and several studies underlining the role of Hsp90 have been carried out. 5,[38][39][40][41] In this respect, the development of drugs based on Hsp90 inhibition could be an important goal in cancer research because multiple proteins involved in tumour progression may be simultaneously inhibited. 42 We have previously showed that Hsp90 is over-expressed in canine OSA tissues, suggesting a role in tumour progression and that in vitro treatment with 17-AAG induced autophagy and apoptosis in D17 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…There are eight members of the gene family: VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E, VEGF-F, and placenta growth factor-1 (PIGF-1) and PIGF-2. It has many functions, including stimulating angiogenesis, recruiting new blood vessels, inflammation, and vascular permeability through angiogenic, which constitutes the most important signal pathway in tumor angiogenesis (Xie et al, 2017). In a recent study, Tan IIA dramatically suppressed; VEGF promoted the migration and tube formation of human endothelia progenitor cells through the phospholipase C (PLC), Akt, and JNK signaling pathways without cytotoxic effect .…”
Section: Tan Iia Inhibits Tumor Angiogenesismentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) and its receptors (VEGFRs) play a critical role in angiogenesis in osteosarcoma. 1 All of the VEGFR-TKIs with a high specificity and strong affinity only had a median PFS of 4-6 months for refractory osteosarcoma, 2,3,5,27-29 suggesting an urgent need for a predictive marker that indicates benefits from VEGFR-TKI. The already explored potential predictive factors included patient-related factors, such as VEGFR gene polymorphisms; 30 tumor-related factors, such as microvascular density, serum VEGF level and VEGFR-2 expression; 31 and drug-related factors, such as treatment-induced hypertension and hand-foot syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The process of angiogenesis is crucial for osteosarcoma growth, invasiveness, and metastasis. 1 Anti-angiogenesis tyrosine kinase inhibitors (TKIs) are effective in prolonging progression-free survival (PFS) for advanced osteosarcoma that has progressed upon firstor second-line chemotherapy. 2,3 In a prospective study on apatinib for advanced osteosarcoma after the failure of traditional multimodal therapy (NCT02711007), apatinib reached 4-month PFS rate of 56.8% for advanced osteosarcoma [4][5][6][7] with a tolerable and manageable safety profile.…”
Section: Introductionmentioning
confidence: 99%